RETRACTED ARTICLE: The comparison of two different protocols ultra-long versus medroxyprogesterone acetate in women with ovarian endometriosis: a prospective randomized controlled trial - Haiyan Guo; Tong Du; Hongyuan Gao; Qianwen Xi; Ling Wu; Qifeng Lyu; Qianqian Zhu (Reproductive Health)
Abstract Background This study aimed to investigate the medroxyprogesterone acetate (MPA) + HMG protocol vs ultra-long gonadotrophin releasing hormone (GnRH) agonist protocol in patients with advanced ovarian endometriosis who received in vitro fertilization (IVF). Methods Three hundred patients with advanced ovary endometriosis who underwent IVF were included, and embryological and clinical outcomes were assessed between March 2017 and September 2017. Patients were divided into MPA + HMG group and 1-month ultra-long GnRHa protocol group. Results Lower hMG dose and shorter medication time were found in the MPA + HMG group than in the GnRHa group (P < 0.05). Follicle to-Oocyte Index was significantly different between MPA + HMG group and GnRHa group (P < 0.001). No differences were found in the ovary response and numbers of mature oocytes, fertilized oocytes and viable embryos. The clinical pregnancy and live birth outcomes were similar between MPA + HMG group and GnRHa group, and these outcomes were independent of fresh or frozen embryo transfer in the GnRHa protocol group. There were no significant differences in the time to embryo transfer, medical cost and adverse effects. Conclusion The number of oocytes retrieved and pregnancy outcomes after MPA + HMG protocol are similar to those after ultra-long GnRHa protocol in women with ovarian endometriosis. MPA + HMG protocol may be an alternative to ultra-long GnRHa protocol for IVF in ovary endometriosis patients. Trial registration The trial was registered in the Chinese Clinical Trial Registry (ChiCTR-INR-17010924) Plain English summary In conclusion, the administration of MPA in COH showed similar number of oocytes retrieved, no premature LH surge, and similar pregnancy and live birth outcomes in patients with advanced ovarian endometriosis undergoing IVF/ICSI as compared to the one-month long protocol. The use of MPA in COH appears to be promising although many questions remain to be elucidated, including the dose and time of progestin priming as well as its possible influence on the oocyte development potential and microenvironment. Given their good tolerability, few metabolic influence, and low cost, progestogens provide a novel alternative to the conventional protocol for patients with endometriosis.